1999
DOI: 10.1093/hmg/8.12.2293
|View full text |Cite
|
Sign up to set email alerts
|

Fully Expanded FMR1CGG Repeats Exhibit a Length-and Differentiation-Dependent Instability in Cell Hybrids That is Independent of DNA Methylation

Abstract: The fragile X syndrome is characterized at the molecular level by expansion and methylation of a CGG trinucleotide repeat located within the FMR1 locus. The tissues of most full mutation carriers are mosaic for repeat size, but these mutational patterns tend to be well conserved when comparing multiple tissues within an individual. Moreover, full mutation alleles are stable in cultured fibroblasts. These observations have been used to suggest that fragile X CGG repeat instability normally is limited to a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 57 publications
0
28
1
3
Order By: Relevance
“…Length-dependent modifiers of repeat instability are common (32)(33)(34)(35). To explore whether ZFN-induced instability depends on the length of the repeat tract, we transfected the zfGCT nuclease into APRT(CAG) 61 CHO cells and human HPRT(CAG) 68 cells.…”
Section: Figmentioning
confidence: 99%
“…Length-dependent modifiers of repeat instability are common (32)(33)(34)(35). To explore whether ZFN-induced instability depends on the length of the repeat tract, we transfected the zfGCT nuclease into APRT(CAG) 61 CHO cells and human HPRT(CAG) 68 cells.…”
Section: Figmentioning
confidence: 99%
“…DNA repair is progressively attenuated during the process of cellular differentiation, 25 possibly leading to differentiation-dependent spontaneous mutations. 26 PIG-A mutations occurring in cells that lack self-renewal capacity (e.g., CFC) will not propagate disease since the average lifespan of these cells is roughly 125 days. 27 This explains why PIG-A mutations in more differentiated cells (e.g., granulocytes) are common in healthy control subjects; however, these data do not explain how clonal expansion of a PIG-A mutant stem cell occurs in patients with PNH.…”
Section: Disruption Of Pig-a In Human and Murine Embryonic Stem Cellsmentioning
confidence: 99%
“…Completely and partially methylated CGG tracts as short as 20 to 100 repeats have also been observed (Allingham-Hawkins et al 1996;Tassone et al 1999;Genc et al 2000). It has been suggested that for both germline and somatic tissues, the absence of CpG methylation may enhance the deletion of (CGG)n repeats (Burman et al 1999;Helderman-van den Enden et al 1999;Salat et al 2000;Wohrle et al 2001). However, it is not clear how methylation might contribute to CGG instability.…”
Section: Cpg Methylation Stabilizes (Cgg)nmentioning
confidence: 99%
“…Alterations in CpG methylation is a candidate modifier of primate repeat stability because many unstable elements are part of or are embedded within large CpG islands. Furthermore, the instability of certain repeats is restricted to specific loci (Richards et al 1996), specific tissues (Anvret et al 1993;Malter et al 1997), or differentiation status (Burman et al 1999;Wohrle et al 2001), or instability occurs only during specific developmental stages (Malter et al 1997;Martorell et al 1997). Because CpG methylation is highly regulated in a tissue-and development-specific manner (Razin and Shemer 1995), its alteration may contribute to repeat instability.…”
mentioning
confidence: 99%
See 1 more Smart Citation